Ferritin - novel uses of a well-known marker in paediatrics - Aleksandra Izabella Rytel; Sandra Ostrowska; Katarzyna Marcinkiewicz; Maryna Krawczuk-Rybak; Małgorzata Sawicka-Żukowska (Termedia Publishing House, 2023)
Serum ferritin is one of the most widely used laboratory tests and is associated with both iron deficiency and iron overload. Currently, more and more attention is paid to the involvement of ferritin in processes other than iron metabolism. Low serum ferritin is unanimously associated with iron deficiency, while elevated serum ferritin may be a consequence of various medical conditions such as iron overload, an inflammatory process, SARS-CoV-2, organ failure, cancer, and endocrine disorders, including metabolic syndrome. We present a review of the literature on the role of ferritin in a variety of less obvious disease states in children.